The NTCP p.Ser267Phe Variant Is Associated With a Faster Anti-HBV Effect on First-Line Nucleos(t)ide Analog Treatment - Wu, Lina; Xu, Wenxiong; Li, Xuejun; Liu, Ying; Wang, Lu; Zhu, Shu; Yang, Fangji; Xie, Chan; Peng, Liang (Frontiers in Pharmacology, 2021)
Abstract： Sodium taurocholate cotransporting polypeptide (NTCP) acts as a cellular receptor for the hepatitis B virus infection of host hepatocytes. Previously, many studies confirmed that the NTCP p.Ser267Phe variant was a protective factor against HBV-related disease progression. We therefore designed this study to investigate whether the NTCP p.Ser267Phe variant exerts an additive anti-HBV effect in chronic hepatitis B (CHB) patients on mainstream NAs treatment. After propensity score matching (PSM), a total of 136 CHB patients were included, among whom 68 were heterozygous carriers and 68 were wild-type controls. Proportions of primary nonresponse, partial virological response, virological breakthrough and hepatitis B reactivation and the HBV DNA clearance rate at each time point were compared using the chi-square test. Kaplan-Meier analysis and matched t-tests were also performed to estimate the speed of viral clearance and serum HBV DNA reduction, respectively. The proportion of primary nonresponse was significantly lower in heterozygous carriers than in wild-type controls (p < 0.001), especially in patients using entecavir (p = 0.013). Specifically, heterozygous carriers achieved HBV DNA clearance faster than wild-type controls (log-rank p = 0.0198). HBV DNA levels were reduced more in heterozygous carriers after 12 weeks (p < 0.001) and 24 weeks (p = 0.006) of treatment, especially among patients using ETV. Here, our study demonstrated that heterozygous mutations in rs2296651 enhanced the antiviral response of first-line NAs and helped to explore the possibility of combining NAs and NTCP blockers for a better anti-HBV effect.